BEST PRACTICE ACCOUNTING SEBAGAI PILAR GOOD GOVERNANCE DALAM PENGELOLAAN KEUANGAN LEMBAGA PENDIDIKAN - Imelia Sahda Salsabilla; Putri Durotul Aniqoh; M. Thoriq Aziz; Abdul Wahid (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of accounting best practices as a pillar of good governance in the financial management of educational foundations in Semarang. The focus of the study includes the application of accounting practices in the financial management of educational institutions, the implementation of the principles of transparency, accountability, and efficiency, supporting and inhibiting factors in the implementation of accounting best practices, and their impact on the quality of financial governance of educational institutions. This study uses a qualitative approach with a case study type. Data collection was conducted through interviews, observation, and documentation. The research participants were the heads of the foundations. Data analysis used the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results show that the implementation of accounting best practices is carried out through the preparation of planning-based budgets, routine recording of financial transactions, preparation of periodic financial reports, and strengthening a more structured financial administration system. The principles of good governance are realized through transparency of financial reports, accountability for the use of funds, and efficient management of school budgets. The main supporting factors include the commitment of foundation leaders, a culture of organizational cooperation, and awareness of public accountability, while inhibiting factors include limited human resources, low digital skills, and an administration system that is not yet fully integrated.